Evidence for spin-to-charge conversion by Rashba coupling in metallic states at the Fe/Ge(111) interface - S. Oyarzún (Nature Portfolio, 2016)
Engineering the interaction between spin and charge is important for the creation of spintronics devices. Here, the authors show that the Rashba effect at a single crystalline Fe/Ge(111) interface produces enhanced spin-charge conversion, which could help develop a spin field-effect-transistor.